2017
DOI: 10.14814/phy2.13543
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PPARGC1A gene expression in trained and untrained human skeletal muscle

Abstract: Promoter‐specific expression of the PPARGC1A gene in untrained and trained human skeletal muscle was investigated. Ten untrained males performed a one‐legged knee extension exercise (for 60 min) with the same relative intensity both before and after 8 weeks of cycling training. Samples from the m. vastus lateralis of each leg were taken before and after exercise. Postexercise PPARGC1A gene expression via the canonical promoter increased by ~100% (P < 0.05) in exercised and nonexercised untrained muscles, but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…RNA extraction, library construction, and sequencing. RNA was extracted from the frozen samples (~20 mg) using an RNeasy mini kit (Qiagen, Hilden, Germany) with DNase treatment (Fermentas, Vilnius, Lithuania), as described elsewhere (32). The RNA concentration was measured in a fluorimeter (Qubit 3.0; Thermo Scientific, Vilnius, Lithuania), and RNA integrity was checked by capillary electrophoresis using a Bioanalyzer 2100 (Agilent, Santa Clara, CA); all samples were at least 7 in RIN.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction, library construction, and sequencing. RNA was extracted from the frozen samples (~20 mg) using an RNeasy mini kit (Qiagen, Hilden, Germany) with DNase treatment (Fermentas, Vilnius, Lithuania), as described elsewhere (32). The RNA concentration was measured in a fluorimeter (Qubit 3.0; Thermo Scientific, Vilnius, Lithuania), and RNA integrity was checked by capillary electrophoresis using a Bioanalyzer 2100 (Agilent, Santa Clara, CA); all samples were at least 7 in RIN.…”
Section: Methodsmentioning
confidence: 99%
“…The anaerobic threshold (AT) of the m. vastus lateralis (measured by electromyography and changes in deoxyhemoglobin content) were evaluated as described previously (Popov et al. ). The initial load, load increment, and knee extension rate were 0 W, 2.5 W/min, and 60 cycles/min, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…All participants provided written informed consent to participate. The study design has been described elsewhere (Popov et al 2017). Briefly, 10 untrained males (median age, 22 years [interquartile range, 21-26 years]; weight, 74 kg [72-79 kg]; and body mass index, 23 kg/m 2 [22-25 kg/m 2 ]) performed a onelegged continuous knee extension exercise at the same relative intensity before and after 2 months of aerobic training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that our results are likely to be specific for the participants recruited and the exercise employed. It has previously been reported that both training and fitness level can affect exercise-induced gene expression 44,45 . Thus, the time courses we have reported cannot be assumed for other populations.…”
Section: Compared 19mentioning
confidence: 99%